Microtus mystacinus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
177. East European Vole Microtus mystacinus French: Campagnol de De Filippi / German: Ostfeldmaus / Spanish: Topillo europeo oriental Other common names: Russian Vole, Sibling Vole, Southern Vole Taxonomy. Arvicola mystacinus De Filippi, 1865, Lar Valley, N Iran. Microtus mystacinus is in subgenus Microtus and mystacinus species group. It was recognized in 1972 as a distinct species from M. arvalis and subsequently reported under five different names: subarvalis named by M. N. Meyer, V. N. Orlov and E. D. Skholl’ in 1972 (not subarvalis by E. Heller in 1933), epiroticus, rossiaemeridionalis, levis, and mystacinus. It was separated from arvalis based on chromosomal evidence (2n = 54 in mystacinus and 2n = 46 in arvalis) and cross-breeding experiments. The latter failed to produce litters between mystacinus and arvalis. Taxonomic status of mystacinus is also evident from nucleotide sequences. Subspecific taxonomy was never thoroughly assessed. Monotypic. Distribution. N & E Europe (S Finland, Baltic ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 352, DOI: 10.5281/zenodo.6707142 ...